Religion and Disability: Internalizing Disability-Friendly Values at Al-Mustaqim Mosque Yogyakarta - Hastira, Muhammad Fajhriyadi; Jatmika, Sidik (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
This study explores how Al Mustaqim Mosque in Yogyakarta is redefining the role of religious spaces through its commitment to social justice and disability inclusion. By using a qualitative approach, blending personal interviews with disabled worshipers, hands-on observation, and policy review, this research looks at how a mosque truly transforms into a welcoming environment for everyone. The findings show that inclusion isn’t just about one thing; it’s a blend of physical tools (like ramps and Braille Qurans), staff empathy (through literacy training), and inclusive messaging in sermons and social media. Together, these elements empower elderly and disabled congregants to participate actively in community life. However, the study notes that staying consistent is a challenge. To keep the momentum going, the mosque needs more regular disability-themed content and clearer ways for worshipers to share their feedback. To bridge this gap, the researcher proposes a practical model: scheduling regular inclusive sermons, creating direct feedback channels, and inviting people with disabilities to help write religious outreach materials. By connecting theory with real-world practice, this study proves that true inclusion happens when physical access, management heart, and religious storytelling work as one. Ultimately, this research offers a replicable roadmap for other institutions to follow, ensuring that people with disabilities are not just guests, but active leaders in creating fair and equitable places of worship.